Effectiveness of Digital Health Interventions on Clinical and Behavioral Outcomes in Hypertension Patients: A Systematic Review - Truly Anggraini; Hidayah Karuniawati; Syed Azhar Syed Sulaiman (Lembaga Publikasi Ilmiah Nusantara, 2026)
Hypertension is a major risk factor for cardiovascular disease, yet blood pressure control remains suboptimal, especially in low- and middle-income countries. Digital health interventions (DHI) have been implemented to support hypertension management, although their effectiveness varies. This systematic review evaluated the effects of DHI on clinical and behavioral outcomes in adults with hypertension and identified the most effective type of intervention. Randomized controlled trials (RCTs) published between 2015 and 2025 were searched in PubMed, Scopus, and Google Scholar. Study selection followed the PRISMA guideline, and methodological quality was assessed using the Joanna Briggs Institute (JBI) tool. Fifteen RCTs met the inclusion criteria. Mobile-based interventions were the most frequently studied (8/15; 53.3%) and showed the most consistent benefits, including improved blood pressure control (80%), reductions in systolic (85.7%) and diastolic blood pressure (62.5%), and improvements in medication adherence (100%), self-care behavior (75%), and quality of life (100%). Telephone-based interventions (3/15; 20%) improved target blood pressure attainment and patient satisfaction, whereas web-based interventions (4/15; 26.7%) were generally less effective unless combined with telemedicine or clinical support. Overall, mobile-based DHI demonstrated the most consistent improvements in hypertension outcomes.